NetBeans Platform 6.9 Developer's Guide
The NetBeans Platform has many features provided out of the box for Swing desktop application developers. It can take you hours just to create menu bars, toolbars, a window system, and other typical desktop application infrastructural needs rather than you focusing on your domain knowledge. Imagine how much time you could save with a hands-on guide for using the NetBeans Platform, which relieves you from creating desktop functions for each of your applications.This book guides you through the development of a complete Swing application built on the NetBeans Platform. Each chapter introduces a number of new concepts relating to a theme, such as the window system, and then shows you how to implement the concepts in the application you are creating. At the end of the book you have a task manager, which you can adapt to your own purposes. Or you can, of course, create your own applications, now that you have built up a solid basis of NetBeans Platform knowledge.The NetBeans Platform is a framework for developing large distributed desktop applications. It aims to drastically simplify desktop application development by providing a number of techniques, patterns, and full-blown Swing components out of the box. Most desktop applications have very similar technical requirements, such as: a consistent user interface, extensibility, data display, configuration settings, a help system, distribution mechanisms, on-line update possibilities, and the ability to be deployed to multiple operating systems.